2010
DOI: 10.3109/13693780903154070
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of species and susceptibility of amphotericin B and fluconazole of yeast pathogens isolated from sterile sites in Taiwan

Abstract: To study the demographic changes of yeasts causing invasive infections in Taiwan, especially with respect to species distribution and antifungal susceptibility, we analyzed isolates obtained from four sterile sites of patients in 19 hospitals in 2002 (155 strains) and again from the same hospitals in 2006 (208 strains). Blood was the most common source of the yeasts, accounting for 73.8% of the total isolates, followed by ascites (21.5%), cerebrospinal fluid (3%), and synovia (1.7%). Candida albicans was the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…albicans . This distribution is significantly different from other epidemiological analyses of invasive candidiasis from Taiwan[ 24 , 25 ]. However, another recently reported study showed similar findings and stated that neutropenia is correlated with non- albican Candida infections[ 26 ].…”
Section: Discussioncontrasting
confidence: 96%
“…albicans . This distribution is significantly different from other epidemiological analyses of invasive candidiasis from Taiwan[ 24 , 25 ]. However, another recently reported study showed similar findings and stated that neutropenia is correlated with non- albican Candida infections[ 26 ].…”
Section: Discussioncontrasting
confidence: 96%
“…13 In the Taiwanese TSARY study (data from 1999 to 2006), MIC 90 values were never above 2 lg ml )1 . [14][15][16][17] Finally, among five strains that had caused severe infections, collected in 15 Venezuelan public health centres between 2006 and 2007, MICs were never above 0.5 lg ml )1 . 18 On the other hand, MICs of seven strains from four UK dental hospital departments (from 2000 to 2003) reached higher values than our results (MIC 50 = 1 lg ml )1 ; MIC 90 = 4 lg ml )1 ).…”
Section: Discussionmentioning
confidence: 94%
“…Candida species are ranked fifth among hospital-acquired pathogens [2] and are the fourth most common causative pathogens of nosocomial bloodstream infection (BSIs) [3]. Apart from Candida albicans, other non-albicans Candida, specifically Candida glabrata, Candida parapsilosis and Candida tropicalis, causes fungal nosocomial bloodstream infections [4] and 50% of all non-superficial Candida infections [5]. Interest in the study of antifungal compounds has risen because of increased resistance of fungal pathogens to current antifungal drugs, as well as high levels of toxicity or adverse host reactions of other anti-infective agents.…”
Section: Introductionmentioning
confidence: 99%